2017
DOI: 10.1186/s13046-017-0566-5
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: the spicy modulator of breast carcinogenesis

Abstract: Worldwide breast cancer is the most common cancer in women. For many years clinicians and the researchers are examining and exploring various therapeutic modalities for breast cancer. Yet the disease has remained unconquered and the quest for cure is still going on. Present-day strategy of breast cancer therapy and prevention is either combination of a number of drugs or a drug that modulates multiple targets. In this regard natural products are now becoming significant options. Curcumin exemplifies a promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 105 publications
(112 reference statements)
1
78
0
5
Order By: Relevance
“…It has long been known that phytochemicals play chemopreventive and/or therapeutic roles in various diseases, including cancer. Curcumin in turmeric inhibits cell cycle progression and angiogenesis and induces apoptosis in breast cancer cells . Similarly, polyphenols in wine, tea, or grape juice have been shown to inhibit tumor growth and induce apoptosis in oral cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been known that phytochemicals play chemopreventive and/or therapeutic roles in various diseases, including cancer. Curcumin in turmeric inhibits cell cycle progression and angiogenesis and induces apoptosis in breast cancer cells . Similarly, polyphenols in wine, tea, or grape juice have been shown to inhibit tumor growth and induce apoptosis in oral cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin in turmeric inhibits cell cycle progression and angiogenesis and induces apoptosis in breast cancer cells. 35 Similarly, polyphenols in wine, tea, or grape juice have been shown to inhibit tumor growth and induce apoptosis in oral cancer. 36 In this study, the antiproliferative activity of UA, a triterpenoid, was found to be attributed to caspase-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin significantly inhibits cyclophosphamide-induced regression of human breast cancer xenografts in mice (88,89). In cultures of MCF-7, MDA-MB-231 and BT-474 human breast cancer cells, curcumin may inhibit the ability of camptothecin, mechlorethamine and doxorubicin to induce apoptosis by ≤70% (18,90). Curcumin may also serve as an iron chelator to inhibit hypoxia inducible factor-α prolyl hydroxylase activity (91).…”
Section: Potential Risks and Adverse Side Effects Of Curcuminmentioning
confidence: 99%
“…The polyphenolic phytochemical curcumin [1,7-bis(4-hydroxy-3-methoxyphenyl)-1, 6-heptadiene-3,5-dione; Fig. 1], isolated from the powdered rhizome of Curcuma longa L. (Zingiberaceae) (17,18), interacts with numerous biological targets, including inflammatory mediators, growth factors, enzymes, carrier proteins, metal ions, tumor suppressors, transcription factors, oncoproteins and cellular nucleic acids (19)(20)(21). Discovered in 1815 by Vogel and Pelletier as a yellow pigment (4), curcumin has been consumed for >2,000 years in Asian countries, due to its various medicinal properties against human diseases, including cancer and auto-immune diseases (10,17,(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these results coincided with multiple previous reports on the antiproliferative effect of curcumin in vitro conditions. 27,28 Now, as the cancer cells attain uncontrolled cell growth, the effect of curcumin on the messenger RNA (mRNA) expression of cyclin-dependent kinase (CDK) inhibitor like p21 was assessed. We observed that curcumin caused a significant increase in the relative expression of p21 mRNA ( Figure 1A) as well as p21 protein ( Figure 1B and 1C) in all four cell lines after 24 hours.…”
Section: Effect Of Curcumin On P21 Expressionmentioning
confidence: 99%